Pertanggungjawaban Hukum Orang Tua dalam Tindak Pidana Inses - Putri, Dina Wanda Setiawan; Kusnadi, Sekaring Ayumeida (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to examine the legal responsibility of parents in incest crimes in Indonesia and to evaluate the effectiveness of existing laws and regulations in preventing and handling these crimes. This study uses a normative legal approach with legislative and conceptual research methods. The main data sources are primary legal materials, such as Article 8 of Law Number 1 of 1974 concerning Marriage and Article 76D of Law Number 35 of 2014 concerning Child Protection, as well as secondary legal materials in the form of literature, journals, and other related documents. Data collection techniques are carried out through document studies, while data analysis is carried out in a normative legal manner to understand, criticize, and interpret applicable legal regulations. This study found that although existing regulations have prohibited and criminalized incest, such as in Article 8 of the Marriage Law and Article 76D of the Child Protection Law, the sanctions applied are considered not strict enough to provide a deterrent effect. The application of castration and the installation of electronic chips, as regulated in the Child Protection Law, has also raised controversy regarding human rights. This study emphasizes the importance of strengthening the legal system through revision of laws that provide more effective sanctions and include comprehensive protection for incest victims. The originality of this study's findings lies in the critical analysis of legal loopholes in legislation and recommendations for restorative justice-based solutions that have not been widely reviewed in previous studies.